A Quantity Optimization Method on Integrated-Loading-and-Unloading-Missile Vehicles - LIU Ai-zhen; CHEN Li-yun; WANG Yin-long; Wang Lu (Institute of Advanced Engineering and Science, 2013)
In this paper, an optimization method based on Genetic Algorithm is proposed to solve the integrated-loading-and-unloading-missile vehicle assignment problem. On the basis of analyzing the characters of high cost, low usage and real time loading with missile and the vehicle, the mathematical model was built with the bi-objective of cost and loading time. And the resolving method based on Genetic Algorithm was specially designed to get the optimum allocation scheme. Considering particularity of the problem, variable-list encoding method and valid initial population generation method, special one chromosome cross genetic operator; special one chromosome greedy-and-balanced migration operator and mutation operator are proposed. Simulation results show that the solutions by this algorithm can complete all loading tasks, and also can get an optimum balance between cost and loading time of missiles, which can meet the character of accurate support during wartime. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1985